Owl Creek and distant windmills - Kaplan, Nicole, photographer (Colorado State University. Libraries, 2009)
Wide view of cottonwoods along upper Owl Creek on SGS, with windmills on buttes in distance.
Keywords: buttes; SGS; cottonwoods; landscapes; windmills; Owl Creek